2022
DOI: 10.1016/j.asmr.2021.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation and Return to Sport After Medial Patellofemoral Complex Reconstruction

Abstract: The medial patellofemoral complex (MPFC) consists of the medial patellofemoral ligament and medial quadriceps tendon femoral ligament, which play a critical role stabilizing the patella against lateral translation. After a patellar dislocation, athletes with recurrent dislocations have functional limitations that may limit their return to their prior level of competition, requiring surgical reconstruction. Although ample literature exists delineating return-to-play (RTP) considerations after anterior cruciate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The primary aim of treatment, for both surgery and rehabilitation, is to restore patellar stability, enable normal everyday function and allow participation at the individual patient's desired level of activity [ 3 , 10 , 33 , 62 ]. Given that the disorder predominantly affects adolescents and young adults, many seek to return to—or even excel in—previous activities after surgery.…”
Section: Surgery For Some Rehabilitation For Allmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary aim of treatment, for both surgery and rehabilitation, is to restore patellar stability, enable normal everyday function and allow participation at the individual patient's desired level of activity [ 3 , 10 , 33 , 62 ]. Given that the disorder predominantly affects adolescents and young adults, many seek to return to—or even excel in—previous activities after surgery.…”
Section: Surgery For Some Rehabilitation For Allmentioning
confidence: 99%
“…Given that the disorder predominantly affects adolescents and young adults, many seek to return to—or even excel in—previous activities after surgery. Hence, comprehensive rehabilitation, including regular functional testing is important to facilitate patients in achieving their goals [ 5 , 33 , 44 ]. The knowledge base on functional assessment and rehabilitation before and after surgery is, however, sparse [ 13 , 30 , 33 ].…”
Section: Surgery For Some Rehabilitation For Allmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] Prevalent in obese adolescent females, this population frequently includes congenital pathological changes such as high patella, increased anterior femoral inclination, and femoral talus dysplasia. [2–5] Epidemiological surveys have found that the incidence of patellar dislocation can be as high as 43/100,000 and is mostly associated with young women. [6,7] The clinical symptoms are mainly pain (aggravated by going up and down stairs, squatting), instability (weakness, limpness), knee strangulation, recurrent swelling and movement disorders (afraid to run and jump or easily fall down).…”
Section: Introductionmentioning
confidence: 99%